KEDUDUKAN WASIAT BERDASARKAN KOMPILASI HUKUM ISLAM DAN KUHPERDATA (Study Komparatif) - Arpin Arpin (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
The aim of this study is. To broaden the author in connection with the issue of the Position will Compilation of Islamic Law and the Civil Code as well as handy for reading material for students within the Faculty of Law Universitas Muslim Indonesia in particular those who intend to explore the science of law with regard to research wills. To be input either to the government. In the preparation of legislation and the public who intend to want to know about wills. Authentically the law governing the wills specified in three types: olografis wills, probate is not secret, and the secret testament (closed). Each of these types will have different legal force. Probate is not something that is eternal, that will be revoked and or fall on its own.